Effects of a dexmedetomidine constant rate infusion and atropine on changes in global perfusion variables induced by hemorrhage followed by volume replacement in isoflurane-anesthetized dogs - Candido, Thasa D. [UNESP]; Teixeira-Neto, Francisco J. [UNESP]; Diniz, Miriely S. [UNESP]; Zanuzzo, Felipe S. [UNESP]; Teixeira, Lidia R. [UNESP]; Fantoni, Denise T. (Amer Veterinary Medical Assoc, 2014)
Objective-To evaluate the effects of a dexmedetomidine constant rate infusion (CRI) and atropine on changes in global perfusion variables induced by hemorrhage and volume replacement (VR) in isoflurane-anesthetized dogs.Animals-8 adult dogs.Procedures-Each dog was anesthetized twice, with a 2-week interval between anesthetic sessions. Anesthesia was maintained with 1.3 times the minimum alveolar concentration of isoflurane with and without dexmedetomidine (1.6 mu g/kg, IV bolus, followed by 2 mu g/kg/h, CRI). Dogs were mechanically ventilated and received an atracurium neuromuscular blockade during both sessions. During anesthesia with isoflurane and dexmedetomidine, atropine was administered 30 minutes before baseline measurements were obtained. After baseline data were recorded, 30% of the total blood volume was progressively withdrawn and VR was achieved with an equal proportion of autologous blood.Results-Following hemorrhage, cardiac index, oxygen delivery index, and mixed-venous oxygen saturation were significantly decreased and the oxygen extraction ratio was significantly increased from baseline. The anaerobic threshold was not achieved during either anesthetic session. When dogs were anesthetized with isoflurane and dexmedetomidine, they had a significantly lower heart rate, cardiac index, and mixed-venous oxygen saturation during VR than they did when anesthetized with isoflurane alone. Plasma lactate concentration, mixed venous-to-arterial carbon dioxide difference, base excess, and anion gap were unaltered by hemorrhage and VR and did not differ between anesthetic sessions.Conclusions and Clinical Relevance-Results indicated that the use of a dexmedetomidine CRI combined with atropine in isoflurane-anesthetized dogs that underwent volume-controlled hemorrhage followed by VR did not compromise global perfusion sufficiently to result in anaerobic metabolism.